2015
DOI: 10.1208/s12248-015-9774-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake Mechanism of Paclitaxel Nanocrystals Determined by Confocal Imaging and Kinetic Measurement

Abstract: Abstract. Nanocrystal formulation has become a viable solution for delivering poorly soluble drugs including chemotherapeutic agents. The purpose of this study was to examine cellular uptake of paclitaxel nanocrystals by confocal imaging and concentration measurement. It was found that drug nanocrystals could be internalized by KB cells at much higher concentrations than a conventional, solubilized formulation. The imaging and quantitative results suggest that nanocrystals could be directly taken up by cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…In addition, the small size may have helped PNC to enter cells. A recent study supports that drug nanocrystals could be endocytosed as solid particles [35]. …”
Section: Resultsmentioning
confidence: 93%
“…In addition, the small size may have helped PNC to enter cells. A recent study supports that drug nanocrystals could be endocytosed as solid particles [35]. …”
Section: Resultsmentioning
confidence: 93%
“…7), suitable for intracellular imaging. It is well established that an organic dye such as rhodamine B can be stably incorporated in organic crystal lattice with minimal change in crystallization behavior [29], and NC similarly doped with fluorescent dyes have previously been used to visualize their cellular uptake [46]. To ensure that the incorporated rhodamine B represents Cim-F-alb, free rhodamine B was tested in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Sonvico et al showed that dextran coatings on maghemite NPs can achieve comparable disaggregation properties to PEG coatings and can be used to conjugate targeting moieties . It has also been shown that surface modifications can significantly affect the dissolution kinetics of pure drug NPs . Stiffness and surface texture are also known impact the in vivo performance of NPs .…”
Section: Preparation and Characterization Of Nanocrystalsmentioning
confidence: 99%